The Method of Silent Substitution for Examining Melanopsin Contributions to Pupil Control - Spitschan, Manuel; Woelders, Tom (Frontiers in Neurology, 2018)
The human pupillary light response is driven by all classes of photoreceptors in the human eye — the three classes of cones, the rods, and the intrinsically photosensitive retinal ganglion cells (ipRGCs) expressing the photopigment melanopsin. These photoreceptor classes have distinct but overlapping spectral tuning, and even a monochromatic light with a wavelength matched to the peak spectral sensitivity of a given photoreceptor will stimulate all photoreceptors. The method of silent substitution uses pairs of lights to selectively stimulate a given class of photoreceptors while keeping the activation of all others constant. In this primer, we describe the method of silent substitution and provide an overview of studies that have used it to examine inputs to the human pupillary light response.